1987
DOI: 10.1002/j.1460-2075.1987.tb04774.x
|View full text |Cite
|
Sign up to set email alerts
|

An opsin gene that is expressed only in the R7 photoreceptor cell of Drosophila.

Abstract: Communicated by M.Ashburner previously mentioned oligonucleotides. The complete DNA sequence of the R7-specific opsin gene and its 5' and 3' flanking regions was determined. It is quite different from other known Drosophila opsin genes, in that it is not interrupted by introns and shares only 37-38% amino acid identity with the proteins encoded by these genes. The predicted protein structure contains many characteristics that are common to all rhodopsins, and the sequence differences help to identify four doma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
39
0

Year Published

1989
1989
2016
2016

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 101 publications
(39 citation statements)
references
References 55 publications
0
39
0
Order By: Relevance
“…Reconstitution of Drosophila R7-specific opsin expression patterns using Rh3-1acZ and Rh4-1acZ fusions RNA blot analysis has previously shown that in the adult, Rh4 is expressed exclusively in R7 photoreceptor cells and Rh3 is expressed predominantly in R7 cells (Fryxell and Meyerowitz 1987;Montell et al 1987;Zuker et al 1987}. Rh3 transcripts were also detected at lower abundance in sevenless (sevJ heads, which lack all R7 photoreceptors, and at trace levels in adult body tissues.…”
Section: Resultsmentioning
confidence: 99%
“…Reconstitution of Drosophila R7-specific opsin expression patterns using Rh3-1acZ and Rh4-1acZ fusions RNA blot analysis has previously shown that in the adult, Rh4 is expressed exclusively in R7 photoreceptor cells and Rh3 is expressed predominantly in R7 cells (Fryxell and Meyerowitz 1987;Montell et al 1987;Zuker et al 1987}. Rh3 transcripts were also detected at lower abundance in sevenless (sevJ heads, which lack all R7 photoreceptors, and at trace levels in adult body tissues.…”
Section: Resultsmentioning
confidence: 99%
“…The minor opsins expressed in the central R7 and R8 photoreceptor cells are coordinately expressed in nonoverlapping subsets of cells. Rh3 and Rh4 are ultraviolet-absorbing visual pigments expressed in ∌30 and 70% of the R7 cells respectively in a seemingly randomly pattern of distribution [42][43][44][45]. As with the R7 cells, the same relative proportions of R8 cells, 30 and 70%, express the blue (Rh5) and green (Rh6) absorbing pigments, respectively [46][47][48].…”
Section: Diversity Of Drosophila Rhodopsinsmentioning
confidence: 99%
“…To determine whether the choice of axon target of a svp mutant R1/R6 is appropriately correlated with the rhodopsin it expresses, we used Rh-lacZ transgene reporter constructs that reflect normal rhodopsin expression patterns (Papatsenko et al, 2001); whereas rhodopsin proteins are restricted to the retina, ␀-galactosidase expression is detectable in the axon, allowing us to score target selection and Rh-lacZ expression simultaneously. In wild type, 30% of R7s express Rh3 and 70% express Rh4, while 30% of R8s express Rh5 and 70% express Rh6 Montell et al, 1987;Fryxell and Meyerowitz, 1987;Fortini and Rubin, 1990;Chou et al, 1996;Papatsenko et al, 1997;Huber et al, 1997;Chou et al, 1999). We found that 67% (94/141) of svp mutant R1/R6s that target the R8 layer expressed Rh6-lacZ and 47% (30/64) expressed Rh5-lacZ (Fig.…”
Section: Research Articlementioning
confidence: 99%